Strategic Maneuvering of Criticizing in Mitt Romney’s Speech: A CDS - Idan, abbas (Journal of College of Education, 2023)
the current study examines the realization of the criticizing moves that the speaker in hand conducts to convince his hearers of his political amelioration, in opposition to his opponents' deterioration. The discursive moves tackled in the current study are manifested as strategic maneuvering of criticizing in discourse, extracted from Mitt Romney's speech (US Senator) in his election campaign in 2011. The main tenet derived from the data analysis is that the speaker conducts a manipulative discursive strategies to persuade the hearers of his policy, and gain political advocacy and support. The study aims at investigating the discursive moves that frame the strategic maneuvering of criticizing. The study also sheds light on the ideological tendencies derived from the text. The study is qualitative in trend and comes out with a set of moves, manifesting the textual framing of the criticizing strategies which the speaker manipulates in the text to convince his hearers of his good deeds and the mischievous intentions and deeds of his opponents, represented by Obama and his party. These criticizing strategies are: trigger of problem, problem exhibition, figure of problem, suggestion for solution and promising for solution.